2014
DOI: 10.5603/fhc.2013.0042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E and selenium against aluminum-induced nephrotoxicity in pregnant rats

Abstract: Kidney is one of the most affected organs by aluminium toxicity. This study aimed to investigate the effect of aluminium chloride on the kidney of pregnant rats and to assess the efficiency of vitamin E and selenium in ameliorating this effect. Forty virgin albino rats were randomly divided into two main groups. Control rats were further divided into negative control group (C1, n = 10) which received distilled water and positive control group (C2, n = 10) that received vitamin E (VE, 150 mg/kg/day) and seleniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Parallel to their results, we also found that Vit E was efficacious to prevent the nephrotoxic effects of ZA. Similar results have been reported for Vit E in preventing the nephrotoxicity in rats induced by gentamicin [ 31 ], aluminum [ 32 ], colistin [ 33 ] and mercuric chloride [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…Parallel to their results, we also found that Vit E was efficacious to prevent the nephrotoxic effects of ZA. Similar results have been reported for Vit E in preventing the nephrotoxicity in rats induced by gentamicin [ 31 ], aluminum [ 32 ], colistin [ 33 ] and mercuric chloride [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…In further agreement, other studies confirmed that direct or indirect inhibition of MMP-9 activity by Hesperidin resulted in a decrease in renal fibrosis in obstructive nephropathy (Wang et al 2010 ). Another study added that broad-spectrum metalloproteinase inhibitors have been used to treat fibrotic kidney diseases experimentally (Wozniak et al 2021 ) (Abdel-Hamid 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-powered images (×400 magnification) of the four anatomical layers of each kidney were taken separately (Leica ICC50 HD, Wetzlar, Germany). To analyse AQP-1, AQP-2 and AQP-4 staining, the regions covered by AQP-1, AQP-2 and AQP-4 staining were calculated by optical density (OD) [ 11 ]. We measured the OD values three times and averaged the results.…”
Section: Methodsmentioning
confidence: 99%